Fast and Simple LC-MS/MS Method for Rifampicin Quantification in Human Plasma - Žane Temova Rakuša; Robert Roškar; Anita Klančar Andrejc; Tina Trdan Lušin; Nataša Faganeli; Iztok Grabnar; Aleš Mrhar; Albin Kristl; Jurij Trontelj (International Journal of Analytical Chemistry)
A simple, fast, and cost-effective LC-MS/MS method for quantification of rifampicin in human plasma was developed and fully validated. The plasma samples containing rifampicin and isotopically labelled internal standard rifampicin D8, were cleaned up using a Captiva ND Lipids filtration plate. Chromatographic separation was achieved on an 1290 Infinity liquid chromatograph coupled to 6460 Triple Quadrupole operated in positive mode on a core-shell Kinetex C18 column (50 × 2.1 mm, 2.6 μm) by gradient elution using 0.1% formic acid in water and acetonitrile as a mobile phase. The proposed method is the fastest method published by now, both in terms of sample preparation (approximately one minute per sample) and chromatographic analysis (total run time 2.4 min). Another key benefit is the outstanding sensitivity and wide analytical range (5-40000 μg/L) with good linearity, accuracy, and precision. The method showed almost complete recovery (92%) and absence of any significant matrix effect as demonstrated by uniform responses from QC samples prepared in blood plasma from 6 volunteers (RSD <5%). The proposed method was successfully applied to rifampicin quantification in 340 patients’ plasma samples, thus demonstrating its suitability for both therapeutic drug monitoring and pharmacokinetic analysis.